Probe studies of plasma in a magnetic well - Boyd, Derek A (Department of Physics, 2023)
A modified theta pinch device proposed by Andreoletti has been investigated. Magnetic field measurements have revealed that the device produces a magnetic well with mirror ratio 1.06. Further magnetic probe measurements have enabled detailed description of the plasma dynamics in the central horizontal plane to be given. A method developed by Lovberg in which the magnetic measurements are coupled with measurements with a double floating electric probe, was used to measure the electron density in certain favourable circumstances.